Construindo pontes: o ensino da história social do trabalho entre a academia e a escola - Barros, Juliana da Silva (2022)
This research was developed with the objective of reflecting on the perspectives of approaching the Social History of Work in History Teaching, in order to broaden the discussions around the importance of teaching the History of Work in Brazil. In order to do so, I resorted to the theoretical and methodological approaches of Social History of Work, mainly to the concept of experience in the Thompsonian perspective, to carry out a study of the basic curriculum of History prescribed by the National Curricular Parameters and by the National Curricular Common Base, counting on the contributions developed by Silva (2015), Sacristan (2000), Cury (2018), Bittencourt (2011) etc. Added to questions raised from the experiences as a teacher in the final years of Elementary School in a private school in the city of Conde - PB. Through this reflection, I realized that the approach in the Teaching of History of a Social History of Work in its current and critical perspective is conditioned to the particular interest of the teacher, because in the national curricula, the traditional approach is maintained, crystallized, which has not yet been reached by advances. historiographies of the area. In this sense, the gap between the Teaching of History and the Social History of Work is perceptible as an important knowledge for basic training, putting teachers in the face of the difficulty of updating this knowledge in a significant and didactic way in the classroom. Based on this problem, I developed a proposal for a didactic intervention, problematizing the use of photography as a didactic tool and as research sources for the Social History of Work in the school space. In approaching the reflections made by Ciavatta (2002), Kossoy (2012) and Mauad (1996), among others, I could see that the photographs, in addition to representing particular characteristics of the Worlds of Work - not accessible through written documents - stimulate the development of identity processes through visual skills, as well as representations of social conceptions of work and workers historically constructed, being therefore a fundamental source for the teaching and learning process of the Social History of Work. Through photographic practice, students can be inserted into the knowledge production process and school and community spaces are transformed into objects of investigation.